Bloqueios atmosféricos e sistemas frontais sobre a América do Sul em cenários de clima futuro - Pedroso, Diego (2014)
The meteorological systems modulate the behavior of rainfall and temperature on large regions and must be correctly simulated by the climate models. The representation of these events should be good for the reliability model to be higher. This research therefore has the primary aim of examining how atmospheric blocks and frontal systems are being detected. Was used for this, the model of the British Center, HadGEM2-ES (Hadley Centre Global Environment Model version 2 Earth System) in two climate change scenarios, RCP4.5 and RCP8.5 in the future (2020-2049) projections series, comparing them with series of reference for the past 30 years (1975-2004). The results will be validated from those already found by other studies. For the blocks, the detection method proposed by Pelly e Hoskins (2003), in which find meridionaly anomalous variations of potential temperature in the dynamical tropopause. Frontal systems were found by frontogenetic function first proposed by Petterssen (1956). Moreover, the study of changes in rainfall, simulated by RegCM4 (Regional Climate Model version 4) model for the South and Southeast regions of Brazil is made. The main results show that there good agreement between the annual cycle and positioning of both systems by the model on past. There is a reduction of blocking systems on Central Pacific (170.0◦W-120◦W) and increased over the same region of the Southeast Pacific (117.5◦W-80◦W) and the Southwest Atlantic (77.5◦W-40◦W) in both future scenarios. The frontal systems, which also show a good agreement in the reference series, have a tendency to increase the frequency in the two studied regions. Likewise the accumulated rainfall simulated on RegCM4 indicating to be more significant in summer, fall and spring seasons and behavior similar to that reported previously for the winter months.